Psychosocial stress accompanied by an unhealthy eating behavior is associated with abdominal obesity in Korean adults: A community-based prospective cohort study - Kim, Minji; Kim, Yangha (Frontiers in Nutrition, 2022)
Psychosocial stress is recognized as a potential modulator of eating behavior. Psychosocial stress also constitutes an independent risk factor for the development of non-communicable diseases. This study examined the gender-stratified associations between perceived stress, eating behavior, and abdominal obesity in 4,411 adults aged 4069 years during a 10-year follow-up of the Korean Genome and Epidemiology Study (KoGES). Psychosocial stress was evaluated using the Psychosocial Well-being Index Short Form (PWI-SF), and eating behavior was analyzed with a focus on the dietary variety score (DVS). The Cox’s proportional hazard model was used to examine the risk of abdominal obesity according to stress levels. Higher stress levels were associated with lower DVS in women. Lower DVS scores were positively associated with the consumption of grains and refined grains but was negatively associated with the consumption of fruits. The DVS was not significantly associated with stress levels among men. Prospectively, the highest tertile of grains and refined grains consumption showed an increased risk of abdominal obesity compared to the lowest tertile in women (HR: 1.36, 95% CI: 1.04-1.78, p < 0.05; HR: 1.28, 95% CI: 1.03-1.59, p < 0.05, respectively). By contrast, in all participants, the highest tertile of fruits consumption decreased the risk of abdominal obesity compared to the lowest tertile (men, HR: 0.56, 95% CI: 0.45–0.70, p < 0.01; women, HR: 0.51, 95% CI: 0.40–0.65, p < 0.01). Furthermore, high stress levels showed a borderline significant association with the risk of abdominal obesity only in women (HR: 1.27, 95% CI: 1.001.59, p < 0.05). These findings suggested that psychosocial stress might contribute to abdominal obesity by interacting with eating behavior represented by a low DVS. The approach to consume a diet with a high DVS might help decrease the risk of abdominal obesity among people in stressful environments.